Influence of catheter thickness on respiratory physiology during less invasive surfactant administration in extremely preterm infants - Gunatilaka, Chamindu C.; Xiao, Qiwei; Bates, Alister J.; Franz, Axel R.; Poets, Christian F.; Maiwald, Christian A. (Frontiers in Pediatrics, 2024)
Introduction: Delivering surfactant via thin catheters (minimal-invasive surfactant therapy (MIST); less invasive surfactant administration (LISA)) has become a common procedure.However, the effect of tracheal obstruction caused by catheters of different sizes on tracheal resistance in extremely low gestational age newborns (ELGANs) is unknown.To investigate the affect of catheters size 3.5, 5 and 6 French on airway resistance in ELGANs of 23-28 weeks gestational age during LISA, we performed calculations based on Hagen-Poiseuille's law and compared these with a clinically and physically more accurate method: computational fluid dynamics (CFD) simulations of respiratory airflow, performed in 3D virtual airway models derived from MRI.The presence of the above catheters decreased the cross-sectional area of the infants' tracheal entrance (the cricoid ring) by 13-53%. Hagen-Poiseuille's law predicted an increase in resistance by 1.5-4.5 times and 1.3-2.6 times in ELGANs born at 23 and 28 weeks, respectively. However, CFD simulations demonstrated an even higher increase in resistance of 3.4-85.1 and 1.1-3.5 times, respectively. The higher calculated resistances were due to the extremely narrow remaining lumen at the glottis and cricoid with the catheter inserted, resulting in a stronger glottal jet and turbulent airflow, which was not predicted by Hagen-Poiseuille.Catheter thickness can greatly increase tracheal resistance during LISAprocedures in ELGANs. Based on these models, it is recommended to use the thinnest catheter possible during LISA in ELGANs to avoid unnecessary increases in airway resistance in infants already experiencing dyspnea due to respiratory distress syndrome.